Simultaneous assessment of rotavirus-specific memory B cells and serological memory after B cell depletion therapy with rituximab (2014)
The mechanisms that contribute to the maintenance of serological memory are still unclear. Rotavirus (RV) memory B cells (mBc) are enriched in IgM + and CD27- subpopulations, which are associated with autoimmune diseases pathogenesis. In patients with autoimmune diseases treated with Rituximab (RTX), some autoantibodies (auto-Abs) decrease after treatment, but other auto-Abs and pathogen-specific IgG Abs remain unchanged. Thus, maintenance of autoimmune and pathogenspecific serological memory may depend on the type of antigen and/or Ab isotype evaluated. Antigen-specific mBc and antigen-specific Abs of different isotypes have not been simultaneously assessed in patients after RTX treatment. To study the relationship between mBc subpopulations and serological memory we characterized total, RV- and tetanus toxoid (TT)-specific mBc by flow cytometry in patients with autoimmune diseases before and after treatment with RTX. We also measured total, RV- and TT-Abs, and some auto-Abs by kinetic nephelometry, ELISA, and EliA tests, respectively. Minor differences were observed between the relative frequencies of RV-mBc in healthy controls and patients with autoimmune disease. After RTX treatment, naïve Bc and total, RV- and TT-specific mBc [IgM+, switched (IgA+/IgG+), IgM+ only, IgD+ only, and CD27- (IgA+/IgG+/IgM+)] were significantly diminished. An important decrease in total plasma IgM and minor decreases in total IgG and IgA levels were also observed. IgM rheumatoid factor, IgG anti-CCP, and IgG anti-dsDNA were significantly diminished. In contrast, RV-IgA, RV-IgG and RV-IgG1, and TT-IgG titers remained stable. In conclusion, in patients with autoimmunity, serological memory against RV and TT seem to be maintained by long-lived plasma cells, unaffected by RTX, and an important proportion of total IgM and serological memory against some auto-antigens seem to be maintained by short-lived plasma cells, dependent on mBc precursors depleted by RTX. © 2014 Herrera et al.